The importance of legal skills nowadays - Ezcurra, Huáscar (2015)
In recent years, the attention of lawyers and Law students in the legal skills has greatly increased.In this round table, the rapporteurs deliberate about their possible limits, regulation and enforcement, and give a vision about the future of the practice of Law.